Iranian epos and kazak literature.Ирандық эпос және қазақ әдебиеті. (Journal of Oriental Studies, 2016)
Works of the great Orient classics have significantly influenced on kazakh folklore and written literature. Many kazakh magic fairy tales are based on the plot and motif of persian-tajik classical literary works,in particular, on the motif of «Shah-narme» by Fyrdousi, «Rustem batir», «Zhusip and Zlikha», «Bahram Gour». They are also «Atumtai», «Nasharvan» and five wonderful collection of works by Navoi. Kazakh tales about Iskander exist in several variants. Chapters from «Shah-narme «,in which are told about heroic deeds of Rustem enjoyed special popularity with kazakhs. They inspired batirs from the kazakh epic legends. Ideas about struggle for freedom, justice, human dignity were always close to the kazakh people.Ұлы шығыс классиктерінің еңбектері қазақ фольклоры мен жазба әдебиетіне едәуір әсерін ти гізді. Көптеген қазақ ертегілері негізін парсы-тәжік әдебиетінің классикалық сарынынан, әсіресе«Шахнама», Фирдауси, «Рүстем батыр», «Жүсіп-Зылиқа», «Бахрам Гур» желісінен алады.
Keywords: iranian epos; razakh folklore; «Shah-narme»; Fyrdousi; «Leila and Majnun»; razakh literature; orient languages and literature; «Шахнаме »; Фирдоуси; «Ләйлі және Мәжнүн »; ирандық эпос; қазақ фольклоры; қазақ әдебиеті; шығыс тілдері мен әдебиеті